Deleterious effects of obesity on physical fitness in pre-pubertal children. Issue 2 (17th February 2016) - Ceschia, Arianna; Giacomini, Stefano; Santarossa, Simone; Rugo, Miriam; Salvadego, Desy; Da Ponte, Alessandro; Driussi, Caterina; Mihaleje, Martina; Poser, Stefano; Lazzer, Stefano
Abstract: The prevalence of obesity in children has increased dramatically during the past decades in Europe and understanding physical fitness and its components in children is critical to design and implement effective interventions. The objective of the present study was to analyse the association between physical fitness (aerobic, speed, agility, power, flexibility and balance) and body mass index (BMI) in pre-pubertal children. A total of 2411 healthy schoolchildren (7–11 years) participated in this study. Anthropometric characteristics and body composition were assessed by skinfold thickness. Physical fitness was measured by nine physical fitness tests: endurance running, 20 m running speed, agility, handgrip strength, standing long jump and squat jump, sit and reach, medicine ball forward throw and static balance. No relevant differences were observed between boys and girls regarding anthropometric characteristics, body composition and physical fitness. However, overweight and obese children showed significantly lower physical fitness levels in endurance running, speed and agility (mean: +18.8, +5.5 and +14.5% of time to complete tasks, respectively), lower limb power normalised to body mass (−23.3%) and balance tests (number of falls: +165.5%) than their normal weight counterparts. On the other hand, obesity did not affect handgrip, throwing and flexibility. In conclusion, increased BMI was associated with lower performance capabilities limiting proper motor skill development, which directly affects the ability of children to take on sports skills. Actions undertaken to promote children's wellness and fitness should be prioritised and introduced early in life with the aim of enhancing physical fitness as well as preventing overweight and obesity.